Ecdysteroidogenesis in Heliothis virescens (Lepidoptera: Noctuidae): Recombinant Prothoracicotropic Hormone and Brain Extract Show Comparable Effects. Issue 3 (21st June 2019) - Nardiello, Marisa; Salvia, Rosanna; Scala, Andrea; Scieuzo, Carmen; Bufo, Sabino Aurelio; Franco, Antonio; Vogel, Heiko; di Somma, Angela; Duilio, Angela; Falabella, Patrizia
Abstract: Prothoracicotropic hormone (PTTH) is a neuropeptide that triggers a cascade of events within the prothoracic gland (PG) cells, leading to the activation of all the crucial enzymes involved in ecdysone biosynthesis, the main insect steroid hormone. Studies concerning ecdysteroidogenesis predicted PTTH action using brain extract (BE), consisting in a complex mixture in which some components positively or negatively interfere with PTTH-stimulated ecdysteroidogenesis. Consequently, the integration of these opposing factors in steroidogenic tissues leads to a complex secretory pattern. A recombinant form of prothoracicotropic hormone (rPTTH) from the tobacco budworm Heliothis virescens (F.) (Lepidoptera: Noctuidae) was expressed and purified to perform in vitro tests in a standard and repeatable manner. A characterization of rPTTH primary and secondary structures was performed. The ability of rPTTH and H. virescens BE to stimulate ecdysteroidogenesis was investigated on the third day of fifth larval stage. rPTTH activity was compared with the BE mixture by enzyme immunoassay and western blot, revealing that they equally stimulate the production of significant amount of ecdysone, through a transduction cascade that includes the TOR pathway, by the phosphorylation of 4E binding protein (4E-BP) and S6 kinase (S6K), the main targets of TOR protein. The results of these experiments suggest the importance of obtaining a functional pure hormone to perform further studies, not depending on the crude brain extract, composed by different elements and susceptible to different uncontrollable variables.